LEGAL PRACTICE IN THE BLOCKCHAIN ERA:: THE USE OF ELECTRONIC EVIDENCE - Grigoryevich Zaprutin, Denis; Nikiporets-Takigawa, Galina; V. Goncharov, Vitaly; Dmitriyevich Sekerin, Vladimir; Evgenievna Gorokhova, Anna (Revista Gênero e Interdisciplinaridade, 2020)
This article examines the current trends in the development of the justice system due to the influence of digitalization in the Russian Federation, expressed in the use of digital technologies that complement the traditional system of evidence. The use of evidence obtained using e-mail, electronic digital signature, electronic documents, etc. is becoming more widespread. The purpose of this article is to study the current state and assess the prospects for using electronic evidence, the nature of which is related to the blockchain technology, in legal practice. Based on the legal provisions of criminal and civil proceedings, the types of electronic evidence that are reduced to written and physical evidence, explanations of persons involved in the case, expert opinions, expert consultations, witness statements, as well as audio and video recordings are systematized. The methods of using electronic evidence in litigation existing in international law enforcement practice are described, which, on the one hand, are limited to their interpretation based on the use of electronic signatures and, on the other hand, the application of the norms of traditional civil, criminal and administrative processes establishing general procedural features for evaluating evidence. The problems of using electronic evidence in Russian legal proceedings are highlighted. The absence of a legally established definition of an electronic document as evidence and the grounds on which it can be attached by the court to the materials of the case under consideration, the discussion on the form in which electronic documents should be presented as evidence, as well as the problems of evaluating digital evidence from the position of admissibility, relevance, and reliability are analyzed